Enzymatic Carboxylation of Resorcinol in Aqueous Triethanolamine at Elevated CO2 Pressure - Daniel Ohde; Benjamin Thomas; Paul Bubenheim; Andreas Liese (Molecules, 2023)
The fixation of CO2 by enzymatic carboxylation for production of valuable carboxylic acids is one way to recycle carbon. Unfortunately, this type of reaction is limited by an unfavourable thermodynamic equilibrium. An excess of the C1 substrate is required to increase conversions. Solvents with a high CO2 solubility, such as amines, can provide the C1 substrate in excess. Here, we report on the effect of CO2 pressures up to 1100 kPa on the enzymatic carboxylation of resorcinol in aqueous triethanolamine. Equilibrium yields correlate to the bicarbonate concentration. However, inhibition is observed at elevated pressure, severely reducing the enzyme activity. The reaction yields were reduced at higher pressures, whereas at ambient pressure, higher yields were achieved. Overall, CO2 pressures above 100 kPa have been demonstrated to be counterproductive for improving the biotransformation, as productivity decreases rapidly for only a modest improvement in conversion. It is expected that CO2 carbamylation intensifies at elevated CO2 pressures, causing the inhibition of the enzyme. To further increase the reaction yield, the in situ product precipitation is tested by the addition of the quaternary ammonium salt tetrabutylammonium bromide.